The Mental State Of The Parents With Children With Cerebral Palsy (Clinical And Psychiatric Research) - Rakhmanov, R. V. (Psychiatry, Neurology and Medical Psychology, 2016)
The article presented the nature of the mental disorders in parents raising children with cerebral palsy, delayed mental and language development. Defined behavioral and psychological reactions of parents on the child diagnosis, and describes the specific clinical and psychological manifestations of mental disorders during education, care and treatment of the child. Thesis there is determined behavioral features state of severe trouble in the acute period of parental leave; depressive, phobic, anxiety and hypochondriacal disorder in the early years of the disease. Based on the data that reflect the mechanisms of mental illness in response to family derealization in parents are invited to provide differentiated comprehensive mental health care to parents on the stages of the treatment of neurological disorders child with cerebral palsy.